Prevention and detection of FDIA on power-network protection scheme using multiple support set. (December 2021) - Das, Tanmoy Kanti; Ghosh, Subhojit; Koley, Ebha
Abstract: Usage of ICT tools for monitoring and control of power networks warrants mechanisms for robust security of supervisory control and data acquisition (SCADA) system against false data injection attack (FDIA) and detection of intruder induced manipulation of sensor information. Motivated by the aim of improving network resilience against FDIA, the present work aims at the twin objectives of providing robustness to one of the principle control actions in power networks i.e. protection relaying against FDIA and early detection of FDIA. In this context, a computationally cheap and economically viable schema based on logical analysis of data(LAD) has been proposed. The proposed scheme identifies a minimal set of secured sensors for which the network observability necessary for fault detection and classification is maintained. While preserving the observability, the mapping between sensor information and network state (healthy/faulty) allows for detecting FDIA and providing immunity to the protection scheme, irrespective of the type and extent of FDIA on the unsecured sensors.